Comparison of transcatheter edge-to-edge and surgical repair in patients with functional mitral regurgitation using a meta-analytic approach - Felbel, D.; Paukovitsch, M.; Förg, R.; Stephan, T.; Mayer, B.; Keßler, M.; Tadic, M.; Dahme, T.; Rottbauer, W.; Markovic, S.; Schneider, L. (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background Evidence regarding favorable treatment of patients with functional mitral regurgitation (FMR) using transcatheter edge-to-edge (TEER) is constantly growing. However, there is only few data directly comparing TEER and surgical mitral valve repair (SMVr). Aims To compare baseline characteristics, short-term and one-year outcomes in FMR patients undergoing mitral valve (MV) TEER or SMVr using a meta-analytic approach. Methods: Systematic database search identified 1,703 studies reporting on TEER or SMVr for treatment of FMR between January 2010 and December 2020. A meta-analytic approach was used to compare outcomes from single-arm and randomized studies based on measures by means of their corresponding 95% confidence intervals (CI). Statistical significance was assumed if CIs did not overlap. 21 TEER and 37 SMVr studies comprising 4,304 and 3,983 patients were included. Results: Patients in the TEER cohort presented with higher age (72.0±1.7 vs. 64.7±4.7 years, p<0.001), greater burden of chronic renal disease (33.8±14.3 vs. 16.8±11.1%, p=0.005) and poorer left ventricular ejection fraction (30.9±5.7 vs. 36.6±5.3%, p<0.001). In-hospital mortality was significantly lower with TEER (3% [95%-CI 0.02–0.03] vs. 5% [95%-CI 0.04-0.07]) and one-year mortality did not differ significantly (18% [95%-CI 0.15-0.21] vs. 11% [0.07-0.18]). NYHA (1.06 [95%-CI 0.87-1.26] vs. 1.15 [0.74-1.56]) and MR reduction (1.74 [95%-CI 1.52-1.97] vs. 2.08 [1.57-2.59]) were comparable between both cohorts. Conclusions: Despite considerably higher age and comorbidity burden, in-hospital mortality was significantly lower in FMR patients treated with TEER, whereas a tendency toward increased one-year mortality was observed in this high-risk population. In terms of functional status and MR grade reduction, comparable one-year results were achieved.